Social Beliefs: Adaptation of J. Duckitt’s Scales - Ольга Александровна Гулевич; Ольга Александровна Аникеенок; Ирина Константиновна Безменова (Psychology. Journal of the Higher School of Economics, 2014)
Social beliefs are notions about the nature of other people, their behavior, and the way one should respond to their actions. Social beliefs include beliefs in dangerous world (a view of society as chaotic, unpredictable, and aggressive) and jungle world (a view of other people as lying and manipulative agents trying to “win against” one). This paper presents the results of a study that aimed to check the structural validity of Russian versions of two scales by J. Duckitt, measuring beliefs in dangerous and jungle world. The participants were University students from Moscow and Kazan region, as well as employees of commercial organizations (N=1938, Mean age=20.2, SD = 4.64). The respondents completed a 12-item Russian version of dangerous world belief scale and a 20-item Russian version of jungle world belief scale. Exploratory and confirmatory factor analyses were used to investigate the structure of the questionnaires. For the dangerous world belief scale, a second-order order factor model (with two first-order factors) for showed the best fit. For the jungle world beliefs scale, a second-order factor model (also with two first-order factors) was developed for a subset of 12 items. The authors discuss the compatibility of social beliefs scales with Russian cultural context.